2017
DOI: 10.1136/tsaco-2017-000128
|View full text |Cite
|
Sign up to set email alerts
|

Preinjury ASA score as an independent predictor of readmission after major traumatic injury

Abstract: BackgroundPatients with trauma have a high predisposition for readmission after discharge. Unplanned solicitation of medical services is a validated quality of care indicator and is associated with considerable economic costs. While the existing literature emphasizes the severity of the injury, there is heterogeneity in defining preinjury health status. We evaluate the validity of the American Society of Anesthesiologists (ASA) Physical Status score as an independent predictor of readmission and compare it to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
1
14
2
Order By: Relevance
“…Unlike prior studies which demonstrated higher rates of hospital readmission in trauma patients, 21 we found no association between higher ASA status and readmission among patients undergoing facial fracture repair. This study also found that ASA classification is associated with longer length of hospital stay in facial fracture repairs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike prior studies which demonstrated higher rates of hospital readmission in trauma patients, 21 we found no association between higher ASA status and readmission among patients undergoing facial fracture repair. This study also found that ASA classification is associated with longer length of hospital stay in facial fracture repairs.…”
Section: Discussioncontrasting
confidence: 99%
“…16 ASA physical status classification has been previously used to predict increased readmission rates for orthopedic trauma and spinal fusion procedures, with the highest risk attributed to those with an ASA score of IV. 19,20 Unlike prior studies which demonstrated higher rates of hospital readmission in trauma patients, 21 we found no association between higher ASA status and readmission among patients undergoing facial fracture repair. This study also found that ASA classification is associated with longer length of hospital stay in facial fracture repairs.…”
Section: Discussioncontrasting
confidence: 96%
“…The trend over time of the patients with an ASA III or ASA IV classification is just as expected based on their lower recovery possibilities because of their comorbidities. This is in line with the results of Tran et al (2017) [53] who showed that pre-injury ASA score is an independent predictor of readmission after a major injury, when assumed that this also leads to a lower health status.…”
Section: Discussionsupporting
confidence: 90%
“…There are several possible explanations on these findings such as the 3 rd quintile had the highest percentage of patients with ASA classification ≥ 3. High ASA classification has been shown to be an independent predictor of readmission after major traumatic injury and general surgery[18,19].…”
Section: Discussionmentioning
confidence: 99%